Experiência e intersubjetividade na prática do crossfit: processos comunicativos e estéticos - CASTRO, Fábio Fonseca de (Universidade Federal Fluminense, 2022)
The article discusses the communicative and intersubjective processes present in a box of CrossFit - a growing sport practice in Brazil - located in Belém, Pará. From an ethnography of ten months duration, it was sought to understand the socialities produced there and their interactional dynamics, typification processes and the sharing of a common aesthetic horizon. We propose a dialogue is sought between Communication, phenomenology and ethnography, understanding that the observed social relations constitute, structurally, communicative phenomena, present in social life through typifications of values and understandings of reality.